2012
DOI: 10.1371/journal.pone.0048606
|View full text |Cite
|
Sign up to set email alerts
|

The Repetitive Domain of ScARP3d Triggers Entry of Spiroplasma citri into Cultured Cells of the Vector Circulifer haematoceps

Abstract: Spiroplasma citri is a plant pathogenic mollicute transmitted by the leafhopper vector Circulifer haematoceps. Successful transmission requires the spiroplasmas to cross the intestinal epithelium and salivary gland barriers through endocytosis mediated by receptor-ligand interactions. To characterize these interactions we studied the adhesion and invasion capabilities of a S. citri mutant using the Ciha-1 leafhopper cell line. S. citri GII3 wild-type contains 7 plasmids, 5 of which (pSci1 to 5) encode 8 relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 48 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…Both strains yielded similar adhesion and invasion rates: 51% (± 7.7) and 49% (± 5.3) of Ciha‐1 cells with adherent spiroplasmas, and 1.2% (± 0.06) and 0.8% (± 0.3) of infected cells for S. citri GII3 and GII3‐9a3 respectively. However, in a previous study we had shown that adhesion of S. citri GII3 to Ciha‐1 cells was optimum in the presence of 5 μg ml −1 cytochalasin D, an inhibitor of actin polymerization (Béven et al ., ). Thus, we further compared adhesion capabilities of S. citri GII3, GII3‐9a3 and GII3‐9a3/pTC2 (GII3‐9a3 complemented by transformation with the wild‐type spiralin gene) in the presence of cytochalasin D. As a control we verified that cytochalasin D had no effect on viability (as determined by cfu counts), helical morphology and motility of the spiroplasmas (data not shown).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Both strains yielded similar adhesion and invasion rates: 51% (± 7.7) and 49% (± 5.3) of Ciha‐1 cells with adherent spiroplasmas, and 1.2% (± 0.06) and 0.8% (± 0.3) of infected cells for S. citri GII3 and GII3‐9a3 respectively. However, in a previous study we had shown that adhesion of S. citri GII3 to Ciha‐1 cells was optimum in the presence of 5 μg ml −1 cytochalasin D, an inhibitor of actin polymerization (Béven et al ., ). Thus, we further compared adhesion capabilities of S. citri GII3, GII3‐9a3 and GII3‐9a3/pTC2 (GII3‐9a3 complemented by transformation with the wild‐type spiralin gene) in the presence of cytochalasin D. As a control we verified that cytochalasin D had no effect on viability (as determined by cfu counts), helical morphology and motility of the spiroplasmas (data not shown).…”
Section: Resultsmentioning
confidence: 97%
“…In these competition assays, adding purified recombinant spiralin resulted in an increased adhesion of spiroplasmas to Ciha‐1 cells, despite a decreased entry. A similar situation was previously reported in the case of adhesin ScARP3d (Béven et al ., ). In these former experiments, competition with a recombinant protein corresponding to the ScARP3d repeat domain also resulted in an increased adhesion and a reduced rate of spiroplasma entry (Béven et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations